Enhancing Morpho-Phonetic Listening Competence through the AIR Learning Model: A Focus on English Past Tense Inflections - Josua Silalahi; Dumaris E. Silalahi; Immanuel Onasis Kha Napitupulu; Tias Bastian Saragih; Joyada Alexander Sinambela (Young Journal of Social Sciences and Humanities, 2026)
This research aims to improve the listening ability of grade IX-4 students at SMP Negeri 5 Pematangsiantar, specifically in identifying regular past tense verb endings (-ed). The background of this study is the students' difficulty in distinguishing /t/, /d/, and /ɪd/ sounds. This study utilized Classroom Action Research (CAR) conducted in two cycles. The subjects were 32 students. Data were collected through listening tests and observations. The results showed a significant improvement. The mean score increased from 47.43 in the pre-test to 80.96 in the post-test of Cycle II. Furthermore, the students' passing rate improved from 16.67% to 74.07%. It is concluded that the Auditory, Intellectually, and Repetition (AIR) model is effective in enhancing students' listening skills and engagement.